2019
DOI: 10.1021/acs.inorgchem.8b02997
|View full text |Cite
|
Sign up to set email alerts
|

Organocopper(III) Phenanthriporphyrin—Exocyclic Transformations

Abstract: phyrin 2 act as suitable organometallic ligands for copper(III), adopting trianionic [CCNN] coordination cores. Under oxidizing conditions, in the presence of methanol, copper(III) phenanthriporphyrin 1-Cu undergoes transformation to copper(III) phenanthriporphodimethene with methoxy substituents attached to two trans meso positions. Addition of acids to 1-Cu yields two isomeric copper(III) isophenanthriporphyrins protonated on one of the meso carbon atoms. Protonation of copper(III) 5,6-dioxophenanthriporphyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 95 publications
2
50
1
2
Order By: Relevance
“…The authors also carried out the demethylation of antiaromatic macrocycle 40 by treating it with H 2 SO 4 to obtain a nonaromatic macrocycle 9,10dioxophenanthriporphyrin 45 in 70% yield. [26] Latos-Grażyński and co-workers synthesized Cu(III) complexes 40.Cu and 45.Cu by reacting 40 and 45 respectively with copper(II) acetate at reflux in o-chlorobenzene (Scheme 8 and 9). [26] The crystal structure of 40.Cu showed that Cu(III) ion was nearly in a square planar geometry and bound to two nitrogen atoms and two carbon atoms of the macrocyclic core.…”
Section: B Porphyrinoids With Two Adjacent Pyrrole Rings Substitutedmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors also carried out the demethylation of antiaromatic macrocycle 40 by treating it with H 2 SO 4 to obtain a nonaromatic macrocycle 9,10dioxophenanthriporphyrin 45 in 70% yield. [26] Latos-Grażyński and co-workers synthesized Cu(III) complexes 40.Cu and 45.Cu by reacting 40 and 45 respectively with copper(II) acetate at reflux in o-chlorobenzene (Scheme 8 and 9). [26] The crystal structure of 40.Cu showed that Cu(III) ion was nearly in a square planar geometry and bound to two nitrogen atoms and two carbon atoms of the macrocyclic core.…”
Section: B Porphyrinoids With Two Adjacent Pyrrole Rings Substitutedmentioning
confidence: 99%
“…The NICS(0) values at the centre of macrocycles were 12.1 ( 40 ) and 12.0 ( 40.H + ), which is consistent with the antiaromatic nature of macrocycles. The authors also carried out the demethylation of antiaromatic macrocycle 40 by treating it with H 2 SO 4 to obtain a nonaromatic macrocycle 9,10‐dioxophenanthriporphyrin 45 in 70% yield …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The3 2-thia-5,6-dioxophenanthrisapphyrin 188 can be considered as the expanded congener of dioxophenanthriporphyrin. [150,151] Further extension of the phenanthrisapphyrin framework by consecutive incorporation of another heterocyclic unit together with alinked meso substituent yielded, instead of the expected phenanthrihexaphyrin(1.1.1.1.1.0), helicenophyrin 189 with an incorporated aza [5]helicene unit (Scheme 31). [152] Them acrocycle was obtained from am ixed condensation of phenanthritripyrrane,d ipyrromethane,a nd p-nitrobenzaldehyde under Lindsey reaction conditions.P henanthrihexaphyrin(1.1.1.1.1.0) was anticipated to be the initial macrocyclic product.…”
Section: Expanded Carbaporphyrinoids With Ap Henanthrene Motifmentioning
confidence: 99%
“…Die schwache Paratropizitätvon 185 wurde vollständig ausgeschaltet, wenn zwei Methoxygruppen von 185 abgespalten wurden und folglich eine spontane Oxidation zum entsprechenden Dioxoderivat 188 erfolgte.Die 32-Thia-5,6-dioxophenanthrisapphyrine 188 kçnnen als erweiterte Kongenere von Dioxophenanthriporphyrin betrachtet werden. [150,151] Die weitere Verlängerung des Phenanthrisapphyrin-Gerüstes durch die konsekutive Einführung einer weiteren heterocyclischen Einheit zusammen mit einem meso-Substituenten führte,a nstatt zum erwarteten Phenanthrihexaphyrin(1.1.1.1.1.0), zum Helicenophyrin 189 mit einer eingebundenen Aza [5]helicen-Einheit (Schema 31). [152] Der Makrocyclus wurde in einer gemischten Kondensation von Phenanthritripyrran, Dipyrromethan und p-Nitrobenzaldehyd unter Lindsey-Reaktionsbedingungen erhalten.…”
Section: Expandierte Carbaporphyrinoide Mit Einer Phenanthren-einheitunclassified